Integrating climate change adaptation into development co-operation : policy guidance - Organisation for Economic Co-operation and Development; SourceOECD (Online service) (Paris : OECD, 2009)
This book provides information and advice on how to facilitate the integration of adaptation into development processes. The objectives of this policy guidance are to: (1) promote understanding of the implications of climate change on development practice and the associated need to mainstream climate adaptation in development cooperation agencies and partner countries; (2) identify appropriate approaches for integrating climate change adaptation into development policies at national, sectoral and project levels and in urban and rural contexts; and (3) identify practical ways for donors to support developing country partners in their efforts to reduce their vulnerability to climate variability and climate change. While efforts to integrate climate change adaptation will be led by developing country partners, international donors have a critical role to play in supporting such efforts.--Publisher's description.
Part I. Understanding the Challenge -- 1. Introduction and scope -- 2. Weather, climate variability and climate change -- 3. Vulnerability of the developing world to climate change -- 4. Adapting to the impacts of climate change -- 5. Operationalising adaptation: from theory to action -- Part II. Integration Climate Change Adaptation at National, Sectoral and Project Levels -- 6. National, sectoral and project levels: introduction -- 7. Integrating climate change adaptation at the national level -- 8. Integrating climate change adaptation at the sector level -- 9. Integrating climate change adaptation at the project level -- Part III. Integrating Climate Change Adaptation at the Local Level -- 10. Introduction to the local level -- 11. Local contexts: rural and urban settings -- 12. Integrating adaptation into local development processes -- 13. Key challenges and priorities for actions -- Annex A. Examples of tools and screening approaches for adaptation to climate change -- Annex B. How to integrate climate change considerations into sectoral policies, plans and programmes through strategic environmental assessment.
Title from PDF t.p. (SourceOECD, viewed Aug. 27, 2009)
Also available in French under the title: Adaptation au changement climatique et coop|ration pour le d|veloppement : document d'orientation.
Includes bibliographical references.
Keywords: Climatic changes -- Government policy; Climatic changes -- International cooperation